A method for nested PCR with single closed reaction tubes. - Yourno, J (Genome Research, 1992)
Toward the goal of reducing diagnostic false positives while retaining high sensitivity, a closed-tube nested PCR procedure has been developed for detecting low-copy-number human immunodeficiency virus (HIV) gag target DNA sequences. Master mix for amplification 2, in a hanging gel matrix at the reaction tube top, remains sequestered from the reaction space of the tube during amplification 1. A severalfold excess of inner over outer primers is built into the procedure to assure the high sensitivity of nested PCR. The master mix for amplification 2 is then introduced into the reaction space by centrifugation, and the second amplification is performed as usual. The closed-tube nested procedure shows sensitivity approaching that of the open-tube control procedure, which detects a single copy of HIV gag target DNA at near-theoretical frequency, typically with microgram yields of specific amplification product.